2019
DOI: 10.28945/4412
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality of Lesbian, Gay, and Bisexual International Students: Impact of Perceived Experiences on Campus Engagement

Abstract: Aim/Purpose: While there are studies that examine the experience of LGB or international students, we are not aware of any study that examines both intersectionalities. In this study, we attempt to be the first to examine the experiences of international LGB students and the resources they utilize on campuses. Background: This research provides an understanding of how this population of students interact with the campus environment, how they perceive the campus climate, and what impact their interaction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Most commonly, queer and intersectionality theories were selected to explore the experiences of queer international students in higher education, with queer theory applied in seven papers and intersectionality theory in ten papers. Specifically, these theories were selected for studies related to campus resources and institutional support for queer international students (see Herridge et al, 2019), the likelihood of participating in education abroad programs and experiences in these programs (see Bryant & Soria, 2015), and how queer international students navigate their classroom experiences (see Nguyen & Yang, 2015). Through these theories queer international students are positioned as individuals often marginalized by cisheteronormative and other dominant systems operating in higher education.…”
Section: Theoretical Perspectives Usedmentioning
confidence: 99%
“…Most commonly, queer and intersectionality theories were selected to explore the experiences of queer international students in higher education, with queer theory applied in seven papers and intersectionality theory in ten papers. Specifically, these theories were selected for studies related to campus resources and institutional support for queer international students (see Herridge et al, 2019), the likelihood of participating in education abroad programs and experiences in these programs (see Bryant & Soria, 2015), and how queer international students navigate their classroom experiences (see Nguyen & Yang, 2015). Through these theories queer international students are positioned as individuals often marginalized by cisheteronormative and other dominant systems operating in higher education.…”
Section: Theoretical Perspectives Usedmentioning
confidence: 99%
“…Prior research has shown that international students experience challenges and stressors when they transition to the United States. Herridge et al (2019) and Oba and Pope (2013) mentioned cultural differences, discrimination, language barriers, and academic and financial problems being the most common stressors among international students. Academically, international students have to adapt to a new learning environment as the education system in the United States could be different and less structured than their home country (Herridge et al, 2019;Wu et al, 2015).…”
Section: International Students' Experiences On Us Campusesmentioning
confidence: 99%
“…Herridge et al (2019) and Oba and Pope (2013) mentioned cultural differences, discrimination, language barriers, and academic and financial problems being the most common stressors among international students. Academically, international students have to adapt to a new learning environment as the education system in the United States could be different and less structured than their home country (Herridge et al, 2019;Wu et al, 2015). In the Western education system, educators tend to emphasize autonomy, critical thinking, and engagement in the learning process whereas in non-Western cultures, students are taught to learn information from their professors who are viewed as experts in the field (Scheyvens et al, 2003).…”
Section: International Students' Experiences On Us Campusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In matters that concern educational research and experiences, poetry is a privileged way of engaging intimately with the reader (Saunders, 2003). While not all doctoral journeys can be described as a positive experience, many of them have fluctuations, and some of them have dramas (Corcelles et al, 2019;Herridge et al, 2019;Ramos and Yi, 2020;Weise et al, 2020). My first doctoral drama was traumatic.…”
Section: Introductionmentioning
confidence: 99%